Fast Fourier transform analysis as a new tool for Olympic rifle coaches - Gladyszewski, G.; Gladyszewska, B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
The aim of this study was to examine the possibility of using data collected with an electronic training system to determine the influence of a shooter`s heartbeat on shooting precision. Shooting sessions of a rifle in prone position were studied with the use of an electronic training system. As a case study, results of an experienced shooter were analyzed. Fast Fourier transform was applied to raw data extracted from the system and then results were interpreted. The spectrum obtained revealed a wide peak at the frequency f = 2.6 Hz that was considered as the second harmonics of the average frequency corresponding to the heartbeat decreasing down to 69 beats/min when releasing a shot. The session finished with a very modest score of 611.3 points. When a small intentional change in the shooter`s equipment (a sling position) was introduced, the spectrum obtained did not reveal any peaks and the shooter reached a much better score of 621.8 points. The use of fast Fourier transform analysis is proposed as a new tool for Olympic rifle shooters and coaches. This new tool does not require any complicated procedures and provides quantitative information on the influence of a heartbeat on the stability of a shooter`s aim.